Exploring Haptoglobin as a Promising Marker for Severe Liver Diseases: A Comprehensive Review - Daria Ziemińska; Rafał Burczyk; Wiktor Wardyn; Martyna Michalska; Karolina Winiarek; Joanna Murawska; Cezary Guzowski; Kornelia Kędziora-Kornatowska (Nicolaus Copernicus University in Toruń, 2024)
Liver damage is a common symptom of many diseases, including metabolic disorders and cancers. Such patient condition requires effective examinations aimed at prompt diagnosis and implementation of the most appropriate treatment for a specific disease. Haptoglobin, the subject of many studies, has proven to be a protein that can be used as a biomarker of liver damage, thereby aiding not only in the diagnosis but also in the treatment, resulting in more favorable prognoses regarding patient longevity and quality of life. The aim of this study is to elucidate the role of haptoglobin as a diagnostic and prognostic biomarker in cases of liver damage. This is a review of scientific literature and analysis of clinical data regarding haptoglobin levels in liver damage were conducted to assess the reliability of haptoglobin as a biomarker.This paper primarily utilized the latest publications produced after 2015. PubMed and Google Scholar were used to find relevant publications. All cited works provided useful information to achieve the aim of our article. Analysis of the literature suggests that haptoglobin levels may be significantly associated with the development and severity of liver damage. It may serve as a suitable biomarker for diagnosing diseases that coincide with hepatocyte damage, thus improving the diagnosis of these diseases and increasing the chance of appropriate treatment, which may contribute to prolonging and improving the patient's quality of life. Haptoglobin appears to be a promising biomarker in liver damage; however, further research is necessary to confirm its diagnostic and prognostic accuracy. Haptoglobin exists in various genotypic forms, each characteristic of different disease entities. Understanding the mechanisms regulating haptoglobin levels may lead to a better understanding of liver damage pathogenesis and the development of more effective therapies, increasing the chance of patient recovery and improving their quality of life.